Superfícies Helicoidais no espaço Euclidiano e de Minkowski - SOUZA, Danillo Flugge de (2012)
In this work, based in [2] and [6] we studies helicoidal surfaces of the Euclidean space and Minkowski space R31 with prescribed Gaussian or mean curvature given by smooth functions. In the Minkowski space we consider three especial kinds of helicoidal surfaces, corresponding to the space-like, time-like or light-like axes of revolution and show some geometric meanings of the helicoidal surfaces of the space-like type. We also define certain solinoid (tubular) surfaces around a hyperbolic helix in R31and we study some of their geometric properties.